Selection of early maturing and high yielding mutants of Toraja Local Red Rice Grown from M2-M3 Population after Ion Beam Irradiation - Sjahril, Rinaldi; Trisnawaty, A. R.; Riadi, Muhammad; Rafiuddin, Rafiuddin; Sato, Tadashi; Toriyama, Kinya; Hayashi, Yoriko; Abe, Tomoko (HAYATI Journal of Biosciences, 2020)
This study aims to obtain the genotype of local Toraja red rice M2 mutants that have the potential to be developed into early maturing varieties and have high yields. Research carried out with a mass selection method consisting of two irradiation treatments, namely: (1) irradiation with a Carbon ion dose of 150 Gy (PL-C); (2) irradiation with Argon ion dose of 10 Gy (PL-A) and control as a comparison. Selected strains of M2 seed population were planted in experimental strains plus 2 strains as control, each row had 50 plants. Selection is done in two stages. The first stage, the selection is based on the criteria of plant growth components, to select rice plants that have early-middle age characters, dwarf-semi-dwarf, and many tillers. The second stage, selected strains from the scoring method were then grouped based on the degree of similarity with the cluster analysis method. Irradiation with ion beams produces mutants with shorter harvest times than their parents, with the harvest time 16-17 days or 10% shorter compared to their parents. This study produced 10 selected strains, 5 strains of carbon ion and 5 strains of argon ion irradiation treatment, and formed 5 groups with a 90% similarity coefficient.